2018
DOI: 10.1080/02640414.2018.1527673
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a novel optoelectronic device to measure movement velocity, force and power during the back squat exercise

Abstract: This study analysed the validity and reliability of a new optoelectronic device (Velowin) for the measurement of vertical displacement and velocity as well as to estimate force and mechanical power. Eleven trained males with Mean (SD) age = 27.4 (4.8) years, completed an incremental squat exercise test with 5 different loads (<30-90% of their 1−repetition maximum) while displacement and vertical velocity of the barbell were simultaneously measured using an integrated 3D system (3D motion capture system + force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…22,31,33 Recent studies examined the validity and reliability of VW during free-weight HS over a range of intensities. 19,20 Similar to this study, Garcı´a-Ramos et al 20 used the T-F system as the reference method, finding a low fixed bias in MPV between devices during HS (fixed bias = 0.02 by Garcı´a-Ramos vs a fixed bias range = 20.04 to 0.02 in this study). Garcı´a-Ramos et al 20 found a significant proportional bias in the assessment of MPV during HS, observing an underestimation of MPV with increasing MPV, as assessed by VW.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…22,31,33 Recent studies examined the validity and reliability of VW during free-weight HS over a range of intensities. 19,20 Similar to this study, Garcı´a-Ramos et al 20 used the T-F system as the reference method, finding a low fixed bias in MPV between devices during HS (fixed bias = 0.02 by Garcı´a-Ramos vs a fixed bias range = 20.04 to 0.02 in this study). Garcı´a-Ramos et al 20 found a significant proportional bias in the assessment of MPV during HS, observing an underestimation of MPV with increasing MPV, as assessed by VW.…”
Section: Discussionsupporting
confidence: 69%
“…However, it should be considered that assessments conducted in sports science are commonly characterized by the presence of heteroscedasticity. 34 In addition to this study, Laza-Cagigas et al 19 recently performed a comprehensive validity study of VW using the gold standard method to assess both movement velocity and force production (3D motion capture system and force platform, respectively) during free-weight HS. Although these authors did not examine MPV, they did not find neither fixed nor proportional bias in mean velocity (intercept = 20.04 and slope = 1.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The repetition that produced the maximal average value of the mechanical power (calculated from the accelerative portion of the concentric phase, during which the acceleration of the barbell was ≥ − 9.81 m s −2 ) was selected for the analysis. A recently validated (Laza-Cagigas et al 2018) portable single optoelectronic infrared camera system (Velowin, Deportec, Spain) with a fixed sampling frequency of 500 Hz was used to track a retroreflective strip placed at the center of the bar during the three BP repetitions. The device was connected to a computer through a USB interface and the proprietary software (Velowin 1.6.314).…”
Section: Methodsmentioning
confidence: 99%
“…In spite of being a handy and easy to use tool, the utility of the WiiRemote TM to track points is limited to certain lighting conditions and a sampling rate of 100 samples per second [14]; thus new optoelectronic systems have emerged [15,16]. The VeloFlex system (VS) (Deportec, Murcia, Spain) is a new tool that can track up to four markers and provides real-time feedback with zero latency time.…”
Section: Introductionmentioning
confidence: 99%